Extracellular biosynthesis of anti‐Candida silver ‎nanoparticles using Monascus purpureus. (30th October 2015) - El‐Baz, Ashraf F.; El‐Batal, Ahmed I.; Abomosalam, Farag M.; Tayel, Ahmed A.; Shetaia, Yousria M.; Yang, Shang‐Tian
Abstract : An eco‐friendly process for the silver nanoparticles (Ag‐NPs) biosynthesis was investigated using the fungus Monascus purpureus as a safe and commercially used microorganism. M. purpureus growth filtrate was used for the reduction of the aqueous silver nitrate into Ag‐NPs with almost 100% size range of 1–7 nm, which was considered as one of the smallest microbial biosynthesized Ag‐NPs. The biosynthesized Ag‐NPs were structurally characterized using UV, FTIR, DLS, TEM, and XRD. The biosynthesized Ag‐NPs were stable after 3 months with no alteration in shape or size. M. purpureus showed no nitrate reductase activity, whereas its pigments reducing power was decreased after nanoparticles formation indicating its role in the Ag‐NPs biosynthesis. The synthesized Ag‐NPs exhibited strong antimicrobial activity against different bacteria and yeasts species. The anti‐Candida activity of M. purpureus culture filtrate was enhanced in the presence of Ag‐NPs; the maximum increase in microbial inhibition was observed against Candida albicans with 1.73 increased folds of inhibition zones, followed by their activity against C. tropicalis and C. glabrata with 0.919‐ and 0.694‐folds of increase, respectively. The obtained results suggest that the biosynthesized Ag‐NPs offers a promising cost‐effective, eco‐friendly, and an alternative way to the conventional method of synthesis that could have wide applications in medicine.